Jenis-Jenis Tumbuhan Paku (Pteridophyta) di Hutan Tembawang Kemoyu, Dusun Layau, Kabupaten Sanggau - Natalsiani, Yolanda Denisia; Turnip, Masnur; Linda, Riza (Agroprimatech, 2024)
Ferns (Pteridophyta) have an important role in maintaining the forest ecosystems, but land use change affects the decline in the number of fern species. This study aims to determine the types of ferns that exist in the Tembawang Kemoyu Forest, area in Layau Hamlet, Sanggau Regency. The research will be conducted from March to September 2023 in the Tembawang Kemoyu Forest area in Layau Hamlet, Sanggau Regency. The research method used is the cruise method. The results of the study found 18 species of ferns consisting of 11 families, namely Asplenium nidus, Drymoglossum piloselloides, Drynaria quercifolia, Nephrolepis bisserata, Phegopteris connectilis, Stenochlaena palustris, Selaginella intermedia, Selaginella willdenowii, Lindsaea ensifolia, Lygodium circinnatum, Pteris vieillardii, Asplenium adiantum, Adiantum latifolium, Taenitis blechnoides, Gleichenia linearis, Vittaria elongata, Elaphoglossum callifolium and Selaginella velutina.